2024
DOI: 10.1177/23259671231223743
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Outcomes Between Modern Augmented ACL Repair and Autograft ACL Reconstruction: A Systematic Review and Meta-analysis of Studies With Minimum 2-Year Follow-up

Yunong Ren,
Jia Wang,
Junjie Ji
et al.

Abstract: Background: Anterior cruciate ligament (ACL) reconstruction has been the gold standard for primary ACL rupture since the 1990s. In the past decade, ACL repair has received renewed attention and increased research. Purpose: To compare the clinical outcomes of modern augmented ACL repair versus autograft reconstruction for ACL ruptures. Study Design: Systematic review; Level of evidence, 3. Methods: A search of the PubMed, EMBASE, Scopus, Web of Science, and the Cochrane Library databases was conducted for prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Yang et al [14] highlighted the efficacy of 6HS autografts in achieving high knee functionality and significantly low re-injury rates, demonstrating their reliability in clinical practice. Recent clinical evaluations, like those by Ren et al [31], observed that patients with 6HS autografts tend to have a faster return to sports and a higher likelihood of regaining pre-injury activity levels compared to those with traditional four-strand grafts. These findings suggest that 6HS autografts facilitate a more effective rehabilitation process, possibly due to their biomechanical properties that closely align with the native ACL [32].…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…Yang et al [14] highlighted the efficacy of 6HS autografts in achieving high knee functionality and significantly low re-injury rates, demonstrating their reliability in clinical practice. Recent clinical evaluations, like those by Ren et al [31], observed that patients with 6HS autografts tend to have a faster return to sports and a higher likelihood of regaining pre-injury activity levels compared to those with traditional four-strand grafts. These findings suggest that 6HS autografts facilitate a more effective rehabilitation process, possibly due to their biomechanical properties that closely align with the native ACL [32].…”
Section: Clinical Outcomesmentioning
confidence: 99%